Analisis Sensitivitas dan Dualitas Program Linear Metode Simpleks untuk Optimalisasi Keuntungan Penjualan Nasi Kuning dan Nasi Goreng - Habibi, Rizki; Panjaitan, Arie Candra; Octariani, Dhia (Indo-MathEdu Intellectuals Journal, 2024)
This study presents a secondary analysis of the optimization of yellow rice and fried rice production at Ibu Hamina's shop using the linear programming method. Previously, optimization was carried out using a graphical method but did not conduct a sensitivity analysis to evaluate the impact of changes in production parameters on the optimal solution. The method used is a more sophisticated simplex method, while simultaneously conducting duality analysis to understand shadow prices and resource efficiency by evaluating the relationship between primal and dual problems, and evaluating the impact of changes in production parameters on optimal solutions by conducting sensitivity analysis. The results of this study show that the optimal solution is achieved by producing 7 packages of yellow rice and 3 packages of fried rice per week, resulting in a maximum profit of IDR 7,350,000.00 per week; which is IDR 1,050,000 higher than the results of previous research. The duality analysis shows the consistency of the optimal value between the primal and dual problems. The sensitivity analysis shows that small changes in parameters can affect the value of the objective function. This study shows that the simplex method is effective in optimizing the production of yellow rice and fried rice, providing a more significant maximum profit